DEVELOPMENT OF ANDROID-BASED MATHSOC LEARNING MEDIA IN MATHEMATICS LEARNING IN MTS WITH THE KODULAR BUILDER APPLICATION - Rohman, Mukhammad Atho'ur; Maarif, Safiil (Jurnal Karya Pendidikan Matematika, 2026)
This study aims to develop an application-based mathematics learning media called MathSoc and determine its level of validity, practicality, and effectiveness in supporting the learning process. The research method used is research and development. The research subjects consisted of students and educators at MTs Al-Hikam. Data collection instruments included questionnaires and tests. The results of the study showed that the MathSoc learning media was declared very valid based on the assessment of three media experts with an average percentage of 95.17% and three material experts with an average percentage of 93.89%. The practicality test involving students and educators obtained an average percentage of 95.83% with a very practical category. Furthermore, the effectiveness test through the N-gain calculation showed a value of 0.7613 with a high category, which was supported by an increase in the average test score of students from 51.03 before treatment to 88.38 after using the MathSoc learning media. Based on these results, it can be concluded that the MathSoc learning media is valid, practical, and effective for use in mathematics learning. This media can improve student learning outcomes and support more engaging, flexible, and student-centered learning. This research is expected to provide an alternative solution in developing application-based learning media to improve the quality of mathematics learning.